Survival rate of Macrobrachium acanthurus (Caridea: Palemonidae) larvae in laboratory conditions under different salinities and diets - Rodrigues, Maria Maschio; De Almeida, Luis Carlos Ferreira [UNESP]; Bertini, Giovana [UNESP] (My University, 2018)
Macrobrachium acanthurus is a native species from Brazil with a considerable economic interest, but there is no technology for its cultivation yet. Thus, the present work is aimed to determine the salinity conditions and the most effective diet for larval development. Zoea I were submitted to two experiments: the first one evaluated the effects of different salinities on survival time in starving larvae; the second experiment larvae were reared using five different diets (Artemia, microalgae, Artemia + microalgae, Artemia + inert diet and inert diet) using the salinity that showed higher survival period from the first experimental setting. Survival curves were calculated according to the Kaplan-Meier method and the multivariate Cox regression checked the effect of food types on larval survival rate. The lowest survival period occurred at a salinity of 0 and 33 gL-1 and the highest at a salinity of 15 gL-1. Artemia and Artemia + inert diet were the most effective diets for larval development and survival, increasing by 281 and 199 times, respectively, the chances of survival compared to the inert diet alone. The results indicate that 15 gL-1 salinity and Artemia diet should be considered for future larviculture of M. acanthurus.

Macrobrachium acanthurus é uma espécie nativa brasileira que possui grande interesse econômico, mas ainda não possui tecnologia para seu cultivo. Assim, o presente trabalho visou determinar a salinidade e a dieta mais eficaz para sua larvicultura. As zoea I foram submetidas a dois experimentos: o primeiro avaliou os efeitos de diferentes salinidades no tempo de sobrevivência das larvas em inanição; no segundo as larvas foram cultivadas em cinco diferentes dietas (Artemia, microalgas, Artemia + microalgas, Artemia + dieta inerte e dieta inerte) utilizando a melhor salinidade encontrada. As curvas de sobrevivência foram calculadas de acordo com o método de Kaplan-Meier e a regressão multivariada de Cox verificou o efeito dos tipos de alimento na taxa de sobrevivência das larvas. Os menores tempos de sobrevivência ocorreram nas salinidades de 0 e 33 gL-1 e o maior na salinidade de 15 gL-1. Os alimentos Artemia e Artemia + dieta inerte foram os mais efetivos para o desenvolvimento e sobrevivência das larvas, aumentando em 281 e 199 vezes, respectivamente, as chances de sobrevivência em relação à dieta inerte sozinha, respectivamente. Os resultados indicam que o uso da salinidade de 15 gL-1 e a alimentação composta por Artemia podem ser considerados em futuras larviculturas de M. acanthurus.
Keywords: Artemia; Camarão-canela; Cinnamon river prawn; Dieta inerte; Inanição; Inert diet; Larvas de camarão; Prawn larvae; Starvation